Teachers’ Perception of Virtual Learning: An Experience from a Teaching Project at the Pacific Campus of the University of Costa Rica - Montero, Rosberly López (2025)
The aim of this study is to understand the perception of virtual learning among the teaching staff of the English with Business Management Training program at the Pacific Campus of the University of Costa Rica. This research stems from the diagnostic phase of the teaching project PD-D-723-2023, "Reflection on the Practices in Virtual Courses of Teachers in the English with Business Management Training Program." The study employs a mixed-methods approach with a sequential explanatory design, where the first instrument is analyzed quantitatively, and the second is analyzed qualitatively through thematic analysis. The first instrument was applied to 26 teachers, and the second to 15, representing the total number of faculty involved with the program at the time of data collection. Key findings reveal that the teaching staff share a similar concept of virtual education and have developed an increasingly positive attitude toward it, opening the door to future research on continuous training in emerging technological trends, such as artificial intelligence. It is concluded that, despite limited experience in designing and delivering virtual courses before the pandemic, the teaching staff have a positive outlook on the incorporation of virtual learning across disciplines. Continuous professional development is recommended to maximize the benefits of virtual education, supported by institutional resources, and the results of this project should be shared with the broader academic community.